Marigold and Orange Skin as Egg Yolk Color Promoting Agents - Hasin, B.M.; Ferdaus, A.J.M.; Islam, M.A.; Uddin, M.J.; Islam, M.S. (International Journal of Poultry Science, 2006)
The research was conducted with natural ingredients and orange skin in the diet of laying pullets to determine the suitability as pigmenting agents of egg yolk for laying chicken The influence of test ingredients on production characteristics of laying pullets, internal and external quality characteristics of eggs were investigated simultaneously. The experiment covered the proximate analysis of marigold, orange skin meal to determine the nutrient concentrations, xanthophylls contents and 7th-12th weeks feeding trail to investigate the yolk pigment availability of marigold and orange skin as well as laying performance of birds. Orange skin and marigold were used for comparing the pigmenting ability to normal feed containing xanthophylls. Yolk color was improved significantly as compared to control for addition of marigold and orange skin during 4th, 8th and 12th weeks of supplementation. Inclusion of marigold and orange skin in the diet of laying pullets did not cause deterioration in natural and external quality of eggs and there were no significant variations with respect to body weight, hen day egg production egg weight and feed conversion. There was no mortality of birds during study period. The results indicates the conclusion that between two natural ingredients marigold contain more xanthophylls (156.32mg/kg DM) than orange skin (83.02mg/kg DM) and use of 4% marigold meal in the diet of laying pullets is enough to produce eggs with yolk color score 11.00 close to 30 mg synthetic pigment/kg diet at the 12th week of supplementation, whereas the birds that received 4% orange skin in the diet were able to produce eggs with yolk color score 5.0. Moreover, use of marigold and orange skin in diet of pullet has no detrimental effect on internal and external quality of egg as well as egg production characteristics. So, marigold can be used more efficiently for egg yolk pigmentation.